GROWTH OF RUBBER PLANT (Hevea Brasiliensis Muell. Arg) ON THE USE OF MATERIALS THAT CAN IMPROVE SOIL FERTILITY - Mahyuddin Dalimunthe; Syamsafitri; Rahmi Dwi Handayani Rambe; Indra Gunawan; Nurhayati (CV. Radja Publika, 2022)
This research was carried out at the PTPN III Sarang Giting plantation, Afdeling II, which is located in Sarang Giting Village, Dolok Masihul District, Serdang Bedagai Regency, North Sumatra Province. Venue Altitude 30m above sea level (asl) and flat land topography. The purpose of this study was to determine the effect of stem circumference and production of rubber plants (Hevea brasiliensis Muell. Arg) on ​​potassium (KCl) combined with agricultural lime (CaCO3) and magnesium (MgSO4) and their effect on the dynamics of soil K levels. This study used a factorial randomized block design (RBD) with 3 (three) factors studied, namely the agricultural lime application factor (C), which consisted of C0 = control and C1 = 1500g/tree/year. The second treatment factor was giving magnesium (M) which consisted of M0 = control, M1 = 1500g/tree/year, M2 = 3000g/tree/year, and M3 = 4500g/tree/year. The third treatment factor was the provision of potassium (K) consisting of K0 = control, K1 = 500g/tree/year, K2 = 1000g/tree/year, and K3 = 1500g/tree/year. The results showed that the administration of potassium combined with the application of agricultural lime and magnesium had a significant effect on the growth parameters of stem circumference. Potassium application combined with agricultural lime and kiserite also had a significant effect on the dynamics of K levels in the soil. However, it did not significantly affect the production of liquid latex